Identifying co-morbid fibromyalgia in patients with systemic lupus erythematosus using the Multi-Dimensional Health Assessment Questionnaire. (October 2020) - Huang, Frank F; Fang, Ray; Nguyen, Matthew H; Bryant, Katherine; Gibson, Kathryn A; O'Neill, Sean G
Objective: Fibromyalgia (FM) is prevalent but often under-recognized in patients with systemic lupus erythematosus (SLE). Patient-reported outcomes (PROs) from the Multi-Dimensional Health Assessment Questionnaire (MDHAQ) can identify co-morbid FM in patients with rheumatic diseases. The present study examined the utility of the MDHAQ in recognizing FM in patients with SLE during routine consultations. Methods: Patients with SLE completed an MDHAQ. FM status was determined by the validated 2016 revision of the ACR 2010/2011 preliminary FM criteria. Individual PROs from the MDHAQ and composite Fibromyalgia Assessment Tool (FAST) indices of the discriminatory PROs were compared between patients with and without FM using Student's unpaired t -test and receiver operating characteristic curve analysis to determine the area under the curve (AUC). The physician's clinical impression of FM was recorded, and the SLE Disease Activity Index was used to assess disease activity. Results: Of 88 patients with SLE, 23 (26%) satisfied the 2016 FM criteria. The FAST3 composite measure of two out of three of pain (≥6/10), joint count (≥16/48) and symptom checklist (≥16/60) correctly classified 89% of patients (AUC=0.90, kappa=0.71). Physician diagnosis demonstrated moderate agreement with the 2016 FM criteria (kappa=0.43) but missed 43% of patients with FM. In the presence of active disease, the FAST3 correctly classified 91% of patients. Conclusions: Co-morbid FM is prevalent in SLE yet often underdiagnosed by physicians. The simple FAST3 index of the MDHAQ provides an easy-to-use self-reported tool to improve identification of FM in patients with SLE.